Hypercoagulability state in hip and knee surgery: influence of ABO antigenic system and allogenic transfusion - Iturbe, Teodoro; Cornudella, Rosa; de Miguel, Roberto; Olave, Teresa; Moreno, José Antonio; Callén, Luis; Gutiérrez, Martı́n (Transfusion science, 1999)
It is well know that people with blood group O have a lower risk for venous thromboembolic disease (VTED) than does the general population. Moreover blood transfusion has been identified as a risk factor for VTED in patients with major trauma. The aim of this work is to investigate the behaviour of several markers of hypercoagulability before and after substitutive surgery of hip and knee in order to evaluate the relationship between the plasmatic levels of these markers, the ABO antigenic system and the allogenic blood transfusion. The plasmatic levels of D dimer (D–D), thrombin – antithrombin complex (TAT), and fragment 1 + 2 of prothrombin (F1 + 2) have been determined by the ELISA method in 79 patients subject to substitutive surgery of hip or knee one day before and one day after surgery. The 41 patients with blood groups different from O had presurgical levels of F1 + 2 higher than those of group O ( p=0.004), while no differences could be found for D–D and TAT. The 28 patients who received allogenic blood presented higher levels of D–D one day after surgery than non-transfused patients ( p=0.043); the practice of transfusion did not modify significantly the levels of TAT and F1 + 2 after surgery. In accordance with these results we suggest that blood group and transfusion are risk factors for hypercoagulability, and therefore we advise for a restrictive policy of transfusion practice. New therapies such as aprotinin should be assayed in order to minimize blood loss.